ANÁLISE DOS INSTRUMENTOS DE AVALIAÇÃO DE INTELIGÊNCIA EMOCIONAL E SUA RELAÇÃO COM A PERCEPÇÃO DO SUCESSO NA CARREIRA - OLIVEIRA, MACLEAN DE (2018)
This study aims to identify the relationships between emotional intelligence and the perception of career success through a quantitative research. A literature review was developed to study the instruments used to measure emotional intelligence, and one of this instrument was selected to be applied in a group of individuals with 5 or more years of career. Also, an instrument to evaluate the perception of career success was applied. In total 93 respondents participated in the study, using the Trait Meta Mood Scale to analyze the emotional intelligence and the Reduced Career Success Perception Scale to analyze the perception of career success. The results showed a weak relation between emotional intelligence and perception of career success.